2014
DOI: 10.1002/2013wr015101
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic dynamics and geochemical responses within a floodplain aquifer and hyporheic zone during Hurricane Sandy

Abstract: Storms dominate solute export budgets from catchments and drive hydrogeochemical changes in the near-stream environment. We captured near-stream hydrogeochemical dynamics during an intense storm (Hurricane Sandy, October 2012), by instrumenting a riparian-hyporheic zone transect of White Clay Creek in the Christina River Basin Critical Zone Observatory with pressure transducers, redox probes, and pore water samplers. In the floodplain aquifer, preferential vertical flow paths such as macropores facilitated rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 69 publications
3
79
0
1
Order By: Relevance
“…A. Vaughan, Belmont, et al, ). This overall pattern is consistent with observed event‐based clockwise hysteresis (Table ), regional prevalence of streambank erosional sources (Dhillon & Inamdar, ), and observations of subsurface storm flow dominating hydrologic pathways (McLaughlin, ; McLaughlin & Kaplan, ; Sawyer et al, ). Further, piecewise regression analysis indicates that although the overall trend increases, at flows above 0.97 m 3 s −1 , the slope of the C‐Q relationship remains positive but decreases relative to smaller event flows (Figure , Table ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A. Vaughan, Belmont, et al, ). This overall pattern is consistent with observed event‐based clockwise hysteresis (Table ), regional prevalence of streambank erosional sources (Dhillon & Inamdar, ), and observations of subsurface storm flow dominating hydrologic pathways (McLaughlin, ; McLaughlin & Kaplan, ; Sawyer et al, ). Further, piecewise regression analysis indicates that although the overall trend increases, at flows above 0.97 m 3 s −1 , the slope of the C‐Q relationship remains positive but decreases relative to smaller event flows (Figure , Table ).…”
Section: Discussionsupporting
confidence: 85%
“…Previous work in White Clay Creek has demonstrated that during baseflow and early stormflow conditions, discharge is generated primarily by deeper groundwater flowpaths including spring seeps and, to a lesser extent, shallow riparian aquifers; this results in a mixture of primarily deep groundwater and lesser contributions of shallower riparian groundwater to the stream on the rising limb (McLaughlin, ; McLaughlin & Kaplan, ; Sawyer et al, ). In contrast, discharge peaks reflect a mixture of groundwater, overland flow, and direct precipitation inputs, whereas discharge on the falling limb is dominated by prolonged drainage from riparian floodplain aquifers (McLaughlin & Kaplan, ; Sawyer et al, ; Figure ). At both event and longer timescales, the patterns of clockwise hysteresis and solute dilution observed for geogenic and exogenous solutes are consistent with this sequence of hydrologic connections between various biogeochemical source areas and the stream.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of high nitrate concentrations above this layer is consistent with potential nitrification under oxidizing conditions, whereas the nonconservative decline in nitrate concentrations below is consistent with denitrification under anaerobic conditions (Table S1). These observations collectively highlight the importance of lithology on subsurface geochemistry in the banks, similar to observations by Sawyer et al () in the nontidal portion of the same river. There, E h in permeable gravel layers varied strongly over time during a major storm but remained moderately stable in less permeable soils.…”
Section: Discussionmentioning
confidence: 99%
“…These drivers can interact and tend to alternately dominate in different settings. Vorenhout, van der Geest, van Harum, Wattel, and Eijsackers () illustrated how lithology controlled the magnitude of redox response to tides, whereas in other settings, E h gradients were surprisingly stable due to the lithology (Sawyer, Kaplan, Lazareva, & Michael, ). Other studies suggest hydrologic variability as the dominant factor, as it is often a direct control of oxygen transport.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, precipitations cause changes in the spatial structure of the HZ by variating river and groundwater levels, and HEF is expected to change accordingly with the oscillation of hydraulic heads and larger-scale patterns of groundwater recharge and discharge (Section 4.1) (Wondzell, 2006). At catchment scale, quick increases of the groundwater table during a precipitation event promote continuous groundwater discharge 20 (Sawyer et al, 2014) and in turn changes hyporheic bank storage (Brunke and Gonser, 1997). After precipitation, stream levels normally rise faster than the groundwater table thus leading to dynamic storage of water in stream banks and floodplains (Krause, 2007;Gulley et al, 2011).…”
Section: Concepts and Terminologymentioning
confidence: 99%